Speech Politeness Principle Violation in Ã¢â‚¬Å“Rumah Uya Trans7Ã¢â‚¬Â - Istriwati, Enita; Rustono, Rustono (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Talk shows on television today are programs that are of interest to television viewers in Indonesia. One of the talk shows that television viewers are interested in is the talk show Rumah Uya Trans7. The show is easily followed by the viewers. The speech acts used in the show are light and easy to understand. Another interesting issue is the speech acts are a violation of the politeness principle. Yet, this violation of the politeness principle is the one that makes the television viewers pay attention to the show. These violations of the politeness principle are very interesting to be analyzed. To find out the violation of the politeness principle in the show, the researcher used the theory of pragmatics and descriptive qualitative method. Data of this research were taken from the fragments of the show in the Rumah Uya Trans7 in November 2018. The source of the data was the speech acts in the program which contained violation of the politeness principle. The method of the research was the observation method (simak bebas libat cakap) and recording as well as note-taking techniques to collect the data. The result of the analysis showed that violation of politeness principle was found in the show in the form of violation of maxim of tact, maxim of sympathy, maxim of agreement, maxim of modesty, maxim of approbation, and maxim of feeling reticence. The suggestion for the deepening of the research is the existence of further research in violation of the politeness principle of similar shows but different television station as e media.